Cough in children with acute respiratory infections: to treat or not to treat? - O. I. Simonova; K. A. Ikonnikova (Лечащий Врач)
The article discusses the methods of therapeutic influence in the case of transport disorders and improvement of the drainage functions of the respiratory tract in acute respiratory infections in children. The mechanism of action of acetylcysteine in the treatment of acute inflammatory diseases of the respiratory tract in children is considered.